Panorama de vida e trabalho dos catadores de materiais recicláveis de Boa Vista - RR - Ferreira, Antonio Ramos (2019)
The recyclable material waste-picker removes from what others discard for their survival in a scenario of worker's discartability intensification of consumerism and consequent narrowing of the gaps between utility and convenience and disutility and rejection. This is a central figure in the scope of the discussions of this research aiming to understand the living and working conditions of waste-pickers from Boa Vista-RR and also provide a better visibility to this group of workers who earns their living from the garbage. The methodological procedures of the present study were identified by their exploratory and descriptive nature regarding to their ends and by their quali-quantitative view to their mean as well as by the use of the dialectical method. Data collection was based on an integrative and bibliographical review and a case study. Data analysis was done using sociological hermeneutics and graphic and geospatial analysis. The results of the research demonstrated that the existence of a field of studies on the recyclable material waste-picker reflects the scale of problematic of subproletarization of such workers, making possible the understanding of a case study in the city of Boa Vista, RR, Brazil where such professionals enter in a marginal or relative way in both the production and consumption markets resulting in low quality of life and work indicators. It can be concluded that recyclable material waste-pickers in Boa Vista have been inserted in a dynamics of exploration of the surplus of work in the current stage of capitalism due to the capital growth through the spoiling of work promoted by very heavy load and unhealthy and precarious working conditions.